Knowledge of anaesthetists in a department of anaesthesiology regarding “do not resuscitate” orders during the perioperative period - Monchwe, Tebogo Benedict (My University, 2022)
Background The ethical principle of autonomy is codified in the constitutional and legislative laws governing South Africa. Patients have the right to refuse life-prolonging or sustaining medical therapies; this is inclusive of their right to have directives indicating orders not to resuscitate in possible critical circumstances. The aim of this study was to assess the knowledge of anaesthetists regarding do not resuscitate (DNR) orders during the perioperative period in the Department of Anaesthesiology at the University of the Witwatersrand. Methods A cross-sectional, contextual research study design was followed using an anonymous self-administered online questionnaire. The study population consisted of anaesthetists working in the department. Convenience sampling was used. An online submission of the questionnaire implied consent. Adequate knowledge was defined as a score of ≥60% as determined by the Angoff method. Results The participants mean (SD) score was 63.5% (11.8%), with seniors obtaining a score of 65.3% (12.4%) and juniors 62.4% (11.2%). This difference was not statistically significant (p=0.262). Of the 83 (57.2%) participants who achieved a pass score, 36 (59%) were seniors and 47 (56%) were juniors. This difference was not statistically significant (p=0.100). Conclusion A mean score of 63.5% was achieved by participants in this study indicating adequate knowledge. However, only 57.2% obtained a pass mark of ≥60%. The majority of participants had limited training and experience regarding DNR orders and therefore the feeling of discomfort while treating these patients as a finding was expected. With an estimated 15% of patients having a living will specifying DNR orders and still choosing to undergo surgical procedures, it is important for the anaesthetist to have training and adequate knowledge of DNR orders.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Medicine in Anaesthesiology to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, 2022